Service use in adolescents at risk of depression and self-harm: prospective longitudinal study - Sayal, Kapil; Yates, Nichola; Spears, Melissa; Stallard, Paul (Social Psychiatry and Psychiatric Epidemiology, 2014)
Purpose Although depression and self-harm are common mental health problems in adolescents, there are barriers to accessing help. Using a community-based sample, this study investigates predictors of service contacts for adolescents at high risk of depression and self-harm. Methods Three thousand seven hundred and forty-nine (3,749) 12- to 16-year-olds in UK secondary (high) schools provided baseline and 6 months’ follow-up data on mood, self-harm and service contacts with a range of primary and secondary healthcare services. Results Although most adolescents at high risk of depression or self-harm had seen their general practitioner (GP) in the previous 6 months, less than one-third had used primary or secondary healthcare services for emotional problems. 5 % of adolescents who reported self-harm had seen specialist child and adolescent mental health services in the previous 6 months. In longitudinal analyses, after adjustment for confounders, both depression and self-harm predicted the use of any healthcare services [adjusted odds ratio (AOR) = 1.34 (95 % CI 1.09, 1.64); AOR = 1.38 (95 % CI 1.02, 1.86), respectively] and of specialist mental health services [AOR = 5.48 (95 % CI 2.27, 13.25); AOR = 2.58 (95 % CI 1.11, 6.00), respectively]. Amongst those with probable depression, 79 % had seen their GP and 5 % specialist mental health services in the preceding year. Conclusions Most adolescents at high risk of depression or self-harm see their GP over a 6-month period although only a minority of them access specialist mental health services. Their consultations within primary care settings provide a potential opportunity for their identification and for signposting to appropriate specialist services.